Medical electronics [Technology 2000 analysis and forecast]. - Roos, M. (IEEE spectrum)
The mystery shrouding the interior of a patient's body lifted a little further last year. One noteworthy step was the simultaneous application of a pair of imaging techniques (not just one) to internal organs and tissues. Another was a virtual approach to endoscopy, enabling physicians to inspect organs for disease without invading the body with a catheter or other device. The most dazzling revelations, though, arose from the race to decode the human genome-that is, to uncover the sequence of each gene's four chemical bases: adenine, thymine, guanine, and cytosine. Late last year, researchers said they had decoded most of the genes on Chromosome 22, and by the spring, 90 percent of the human genome will be decoded. Other cellular techniques have also borne fresh fruit. For example, an application of mass spectroscopy has made it possible to inspect the proteins of a cell all at once, instead of picking them out and analyzing them individually